2020
DOI: 10.1038/s41598-020-70251-3
|View full text |Cite|
|
Sign up to set email alerts
|

Bioprocessing strategies for cost-effective simultaneous removal of chromium and malachite green by marine alga Enteromorpha intestinalis

Abstract: A large number of industries use heavy metal cations to fix dyes in fabrication processes. Malachite green (MG) is used in many factories and in aquaculture production to treat parasites, and it has genotoxic and carcinogenic effects. Chromium is used to fix the dyes and it is a global toxic heavy metal. Face centered central composite design (FCCCD) has been used to determine the most significant factors for enhanced simultaneous removal of MG and chromium ions from aqueous solutions using marine green alga E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The significance of the model and also each parameter was assessed using P-values. As referred by [ 63 ], a low probability ‘p’ value (prob > F < 0.05) indicates a high significance of the analogue coefficient. As tabulated in Table 5 , the ANOVA of the regression model of response (MB degradation) unveiled the higher significance of the model as evident from a small probability value (p < 0) with the calculated Fisher’s F test (F-value = 209.22).…”
Section: Resultsmentioning
confidence: 99%
“…The significance of the model and also each parameter was assessed using P-values. As referred by [ 63 ], a low probability ‘p’ value (prob > F < 0.05) indicates a high significance of the analogue coefficient. As tabulated in Table 5 , the ANOVA of the regression model of response (MB degradation) unveiled the higher significance of the model as evident from a small probability value (p < 0) with the calculated Fisher’s F test (F-value = 209.22).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the RE strategic policy shall cover four key aims: security of energy, social equity, economic benefits, and protection of the environment 89 . Some studies concluded that despite the advantages of biomass as RE source, its utilization may act as an inhibitor for the target (3.9) because it releases carbon monoxide, thereby leading to headache, dizziness, nausea, and premature death 55,90 . In addition, the biomass and other sources, such as solar farms, can affect the ecosystems (target 6.6) because of cutting the wood for biomass energy operation and using the wetland for farms installation 28,91 .…”
Section: Toward Sustainable Re Utilizationmentioning
confidence: 99%
“…Dulla et al 24 documented that the biosorption capability of algae is mainly based on the presence of various functional groups of polysaccharides, proteins and lipids in algae cell walls including amino, carboxylic, hydroxyl and sulfate groups, which serve as adsorption sites for metal ions through a variety of mechanisms including ion exchange, electrostatic forces, and complexation. El-Naggar et al 25 , 26 and Hamouda et al 27 were able to successfully remove textile dyes and heavy metals using various types of algal biomass. Dead algal biomass has proven to be more appropriate as biosorbents than living cells because it requires no nutrients, can be stored and used for extended periods of time, and can be recovered with organic solvents or surfactants 28 .…”
Section: Introductionmentioning
confidence: 99%